The growth hormone–insulin-like growth factor-I axis in the diagnosis and treatment of growth disorders - Blum, Werner F; Alherbish, Abdullah; Alsagheir, Afaf; El Awwa, Ahmed; Kaplan, Walid; Koledova, Ekaterina; Savage, Martin O (Endocrine Connections, 2018)
The growth hormone (GH)–insulin-like growth factor (IGF)-I axis is a key endocrine mechanism regulating linear growth in children. While paediatricians have a good knowledge of GH secretion and assessment, understanding and use of measurements of the components of the IGF system are less current in clinical practice. The physiological function of this axis is to increase the anabolic cellular processes of protein synthesis and mitosis, and reduction of apoptosis, with each being regulated in the appropriate target tissue. Measurement of serum IGF-I and IGF-binding protein (IGFBP)-3 concentrations can complement assessment of GH status in the investigation of short stature and contribute to prediction of growth response during GH therapy. IGF-I monitoring during GH therapy also informs the clinician about adherence and provides a safety reference to avoid over-dosing during long-term management.